Development of Science Learning Material Based on Local Wisdom on Plant Tissues' Structure and Function Topic in Class VIII SMP - ika rusdiana dewi (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2023)
This gacorslot study discusses learning science learning with local wisdom of South Kalimantan. At SMPN 9 Banjarmasin there are no teaching materials that link local wisdom, especially funding the Network Structure and Function Material. Therefore, research on the development of teaching materials based on local wisdom IPA. This study aims to describe: (1) the validity of junior high school science teaching materials based on the results of validation, (2) the practicality of junior high school science teaching materials based on the questionnaire response, and (3) the effectiveness of junior high school science teaching materials based on the test results of students studying. This study uses a 4D development model consisting of defining, designing, developing and implementing. However, at the time of this study only reached the development stage only because of time constraints and limited funds. The results showed the validity of teaching materials obtained a percentage of 89.61% with a very valid category. Practicality of teaching materials is obtained an average of 3.46 with practical categories, and the effectiveness of teaching materials is obtained based on N-Gain calculations which is 0.70 with moderate / effective categories. Based on the results of the assessment and the average value obtained, it can be concluded from the science teaching materials based on local wisdom that are declared very valid, practical, and effective so that they are suitable for use in the learning process.